2008
DOI: 10.1016/j.ijgo.2008.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic factors for the prediction of pre-eclampsia in women with abnormal midtrimester uterine artery Doppler velocimetry

Abstract: Measuring uterine perfusion and angiogenic factors concurrently in the second trimester improved the prediction of pre-eclampsia and IUGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…Since these first publications, a multitude of clinical studies has established the ability of these markers to accurately diagnose and predict preeclampsia [72,73,74,75,76]. Meanwhile, automated tests are available to test for the condition in the clinical setting [77,78,79] (fig.…”
Section: Clinical Role In the Diagnosis And Management Of Preeclampsiamentioning
confidence: 99%
“…Since these first publications, a multitude of clinical studies has established the ability of these markers to accurately diagnose and predict preeclampsia [72,73,74,75,76]. Meanwhile, automated tests are available to test for the condition in the clinical setting [77,78,79] (fig.…”
Section: Clinical Role In the Diagnosis And Management Of Preeclampsiamentioning
confidence: 99%
“…Two nested case-control studies from the Calcium for Preeclampsia Prevention trial conducted by Levine et al [12,25] reported promising ORs for the diagnosis of preeclampsia, but specifically for preterm preeclampsia, based on the maternal serum concentrations of sFlt1 and sEng (highest quartile) and PlGF (lowest quartile) in the second trimester. Since then, several studies have reported on the predictive accuracy of angiogenic factors in the first [14] and second trimester [16,32,37,41,42,45,46,[82][83][84][85][86] of pregnancy. Overall, the sensitivity, specificity, positive and negative likelihood ratios of PlGF, sVEGFR-1 and sEng for all cases of preeclampsia ranged between 59% and 100%, 43% and 100%, 1.4 to infinity, and 0.0 to 0.7, respectively (Conde-Agudelo A., Romero R., and Lindheimer M., in press).…”
Section: Angiogenic and Anti-angiogenic Factors In The Prediction Of mentioning
confidence: 99%
“…Yet, the diagnostic indices and ORs reported in recent studies that evaluated the sFlt1/PlGF ratio were similar to those reported for individual angiogenic factors alone. [37,41,42] Recently, two case-control studies [57,58] reported the diagnostic performance of these analytes at 11 to 13.9 weeks for prediction of preeclampsia. Baumann et al [57] measured the maternal serum concentrations of sFlt-1, sEng and PlGF in women with a normal pregnancy and patients who subsequently developed late-onset preeclampsia (>34 weeks).…”
Section: Angiogenic and Anti-angiogenic Factors In The Prediction Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have examined combination tests. [18][19][20] Diab et al 18 performed a study in pregnant women at 23 weeks of gestation with abnormal uterine artery Doppler. When using abnormal uterine artery Doppler with a plasma sFlt-1 level greater than 614 pg ml À1 , the sensitivity, specificity, PPV and negative predictive value (NPV) were 96, 87, 76 and 98%, respectively.…”
Section: Introductionmentioning
confidence: 99%